Female Reproductive Health Disturbance Experienced During the COVID-19 Pandemic Correlates With Mental Health Disturbance and Sleep Quality - Maher, Michelle; O’ Keeffe, Aedín; Phelan, Niamh; Behan, Lucy Ann; Collier, Sonya; Hevey, David; Owens, Lisa (Frontiers in Endocrinology, 2022)
The COVID-19 pandemic has adversely affected population mental health. Periods of psychological distress can induce menstrual dysfunction. We previously demonstrated a significant disruption in women’s reproductive health during the first 6 months of the pandemic. The present study investigates longer-term reproductive and mental health disturbances. A cross-sectional online survey was completed by 1335 women of reproductive age in April 2021. It included validated standardised measures of depression (PHQ-9), anxiety (GAD-7) and sleep quality (PSQI). 581 (56%) of women reported an overall change in their menstrual cycle since the beginning of the pandemic. There was no change in median cycle length (28 days (28-30)) or days of menses (5 (4-5)), but there was a wider variability in minimum (p<0.0001) and maximum (p<0.0001) cycle length. There was a significant increase in heavy menstrual bleeding, painful periods and missed periods compared to pre-pandemic (all p<0.0001). 64% of women reported worsening pre-menstrual symptoms. Rates of severe depression, anxiety and poor sleep were more than double those from large scale representative community samples. Poor sleep quality was an independent predictor of overall change in menstrual cycle (OR=1.11, 95%CI 1.05-1.18), and missed periods (OR=1.11, 95%CI 1.03-1.19) during the pandemic. Increased anxiety was independently associated with a change from non-painful to painful periods (OR=1.06, 95%CI 1.01-1.11) and worsening of pre-menstrual symptoms (OR=1.06, 95%CI 1.01-1.07) during the pandemic. The COVID-19 pandemic continues to bear a significant impact on female reproductive health. Increased levels of psychological distress and poor sleep are associated with menstrual cycle disruption.